Impact of Diabetes Mellitus on Early Clinical Outcome and Stent Restenosis after Carotid Artery Stenting - Alexandru Achim; Dávid Lackó; Artúr Hüttl; Csaba Csobay-Novák; Ádám Csavajda; Péter Sótonyi; Béla Merkely; Balázs Nemes; Zoltán Ruzsa (Journal of Diabetes Research)
Background. Diabetes mellitus is closely related to both the severity of carotid disease and its outcome after revascularization. Carotid artery stenting (CAS) has emerged as a viable alternative to surgical endarterectomy but little is known about the impact of diabetes after CAS. Methods. A consecutive cohort of 1940 patients undergoing CAS in two institutions was divided into two groups, diabetics and nondiabetics, and major cerebrovascular events (MACCEs) were analyzed at 30 days post-CAS and at 1 year follow-up. Results. There were 730 patients with diabetes, with significantly higher BMI, hypertension, chronic dialysis, and dyslipidemia frequency (p<0.05). There was no significant difference between the two groups in terms of early and late MACCEs (composite of transient ischemic attack, major stroke, myocardial infarction, and death), with an early rate of 3.5% nondiabetics vs. 5.3%, p=0.08 and 2.4 nondiabetics vs. 2.3% diabetics, p=0.1 at 12 months. Overall stroke/death rate in the asymptomatic patients was 2.4%, and the restenosis rate was higher in the diabetes population (2.3% vs. 1%, p=0.04). Conclusion. The presence of diabetes was associated with an acceptable increased periprocedural risk for CAS, but no further additional risk emerged during longer term follow-up. Diabetes may precipitate the rate of early in-stent restenosis.